AB0778 A longitudinal study of the clinical effects of conventional and biologic disease modifying anti-rheumatic drugs in australian rheumatology practice. (23rd January 2014) - Roberts, L.; Tymms, K.; de Jager, J.; Littlejohn, G.; Griffiths, H.; Nicholls, D.; Bird, P.; Hill, J.; McCloud, P.; Zochling, J.; ,
Abstract : Background: The treat-to-target approach in Rheumatoid Arthritis (RA) is broadly accepted, however, outside of trial settings, little is known of the therapeutic impact that a new DMARD/bDMARD prescription has on moving patients from a high/moderate disease activity (HMDA) state to low disease activity or remission. Objectives: To observe the effect of a change in DMARD/bDMARD prescription on disease outcome. Methods: The CEDAR Study is a longitudinal observational study conducted by the OPAL QUMI (Optimising Patient outcomes in Australian rheumatoLogy–Quality Use of Medicines Initiative) consortium. Using a clinical audit program, de-identified and routinely collected clinical data from routine practice was sourced from 20 participating rheumatology practices comprising 42 rheumatologists from across Australia. Patients were included if they had baseline and 6 month (4.5-7.5 month) DAS28-ESRs following the initiation of a DMARD/bDMARD either as monotherapy or in addition to their stable previous therapy. A linear mixed model was used determine the change over time and all medications with adequate sample sizes were included. The percentage reduction of patients in the HMDA category was summarized. Results: Of the 9570 screened RA patients, 3103 met the inclusion criteria; 73% female, mean age 62 years, median disease duration 7 years, and 30% had used a bDMARD. All 7 medications were significantly associated with clinically modest reductions in mean DAS28 (Table ) with the range of mean DAS reduction being 0.20-0.78. At 6 months, the percentage of patients who moved from a HMDA category to low disease activity or remission ranged from 7% for etanercept & adalimumab to 19% for tocilizumab. Conclusions: In a large cohort of unselected community RA patients sourced from across Australia, the initiation of a DMARD/bDMARD was associated with a small but significant reduction in disease activity after 6 months. Improvements in disease activity were substantially smaller than improvements reported in randomized controlled trials of the same medications. Possible explanations include: that community patients, in comparison to trial patients, have more refractory disease; are less adherent; are treated less aggressively perhaps because of comorbidities; and/or have less rigorous follow up. Selection bias may be present in this observational study making inferences drawn from medication comparisons unreliable. Nevertheless, leflunomide and tocilizumab appeared to confer the largest benefit amongst the studied DMARDs and bDMARDs respectively. Acknowledgements: OPAL QUMI is supported by Roche Products Pty Ltd (Australia). Medical writing provided by Dr Joseline Ojaimi from Roche Products. Disclosure of Interest: None Declared